Using large-scale linkage data to evaluate the effectiveness of a national educational program on antithrombotic prescribing and associated stroke prevention in primary care - Liu, Z.; Moorin, Rachael; Worthington, J.; Tofler, G.; Bartlett, M.; Khan, R.; Zuo, Y. (Wiley-Blackwell, 2016)
Background-—The National Prescribing Service (NPS) MedicineWise Stroke Prevention Program, which was implemented nationally in 2009–2010 in Australia, sought to improve antithrombotic prescribing in stroke prevention using dedicated interventions that target general practitioners. This study evaluated the impact of the NPS MedicineWise Stroke Prevention Program on antithrombotic prescribing and primary stroke hospitalizations. Method and Results-—This population-based time series study used administrative health data linked to 45 and Up Study participants with a high risk of cardiovascular disease (CVD) to assess the possible impact of the NPS MedicineWise program on first-time aspirin prescriptions and primary stroke-related hospitalizations. Time series analysis showed that the NPS MedicineWise program was significantly associated with increased first-time prescribing of aspirin (P=0.03) and decreased hospitalizations for primary ischemic stroke (P=0.03) in the at-risk study population (n=90 023). First-time aspirin prescription was correlated with a reduction in the rate of hospitalization for primary stroke (P=0.02). Following intervention, the number of first-time aspirin prescriptions increased by 19.8% (95% confidence interval, 1.6–38.0), while the number of first-time stroke hospitalizations decreased by 17.3% (95% confidence interval, 1.8–30.0). Conclusions-—Consistent with NPS MedicineWise program messages for the high-risk CVD population, the NPS MedicineWise Stroke Prevention Program (2009) was associated with increased initiation of aspirin and a reduced rate of hospitalization for primary stroke. The findings suggest that the provision of evidence-based multifaceted large-scale educational programs in primary care can be effective in changing prescriber behavior and positively impacting patient health outcomes.